2003
DOI: 10.1002/anie.200250842
|View full text |Cite
|
Sign up to set email alerts
|

Entropically Driven Ring‐Opening‐Metathesis Polymerization of Macrocyclic Olefins with 21–84 Ring Atoms

Abstract: The ring-opening-metathesis polymerization (ROMP) of strained cyclic olefins has been studied extensively, [1,2] especially since Grubbs' catalyst 1 [3] and the more recently introduced "second-generation" Grubbs' catalyst 2, [4] both of which are tolerant of many functional groups, became commercially available. The ROMP of strained cyclic olefins is mainly enthalpy-driven.A relatively new type of ring-opening polymerization (ROP) exploits the well-known equilibria between cyclic oligomers and polymers [5][6]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 24 publications
2
99
0
1
Order By: Relevance
“…The ROMP of strained cyclic olefins is mainly enthalpy-driven. 53 On the other hand, less strained cyclopentene is thermodynamically less favored to polymerize. Whereby, the monomer conversion is dependent on the reaction temperature and not the catalyst activity, resulting in a monomer-polymer equilibrium.…”
Section: Resultsmentioning
confidence: 99%
“…The ROMP of strained cyclic olefins is mainly enthalpy-driven. 53 On the other hand, less strained cyclopentene is thermodynamically less favored to polymerize. Whereby, the monomer conversion is dependent on the reaction temperature and not the catalyst activity, resulting in a monomer-polymer equilibrium.…”
Section: Resultsmentioning
confidence: 99%
“…The relevant pathways are illustrated for reaction of a Ru methylidene species (the resting state in RCM of α,ω-dienes) with 1,6-heptadiene as an idealized substrate, chosen as a convenient "stand-in" model to facilitate explicit atom tracking. Evident from this picture is the convergence on Ru-alkylidene intermediates that can undergo ADMET, backbiting RCM, or (depending on concentration) [51,52] ROMP. The findings above indicate that the ADMET pathway indicated with a bold arrow is kinetically dominant, irrespective of reaction temperature, even at high dilution.…”
Section: Methodsmentioning
confidence: 99%
“…An equilibrium can thus be established between macrocycles and oligomers (including cyclooligomers formed by backbiting [50,51]; see next section). In the extreme of high concentration (0.7 M and higher), Hodge and Kamau reported entropically-driven ROMP of macrocycles with 21-84 ring atoms [52].…”
Section: Ring Size and Rcm Ratesmentioning
confidence: 99%
“…Higher cyclooligomers were formed as coproducts even on doubling these concentrations. In the extreme of 700 mM, Hodge and Kamau demonstrated that macrocyclic olefins containing up to 84 ring atoms could be induced to undergo efficient, entropically-driven ROMP [84].…”
Section: Ring-chain Equilibria In Rcmmentioning
confidence: 99%